2020
DOI: 10.2147/ijn.s219647
|View full text |Cite
|
Sign up to set email alerts
|

<p>Crystalline and Amorphous Preparation of Aluminum Hydroxide Nanoparticles Enhances Protective Antigen Domain 4 Specific Immunogenicity and Provides Protection Against Anthrax</p>

Abstract: Introduction: Aluminum salts, although they have been used as adjuvants in many vaccine formulations since 1926, exclusively induce a Th2-biased immune response, thereby limiting their use against intracellular pathogens like Mycobacterium tuberculosis. Methods and Results: Herein, we synthesized amorphous and crystalline forms of aluminum hydroxide nanoparticles (AH nps) of 150-200 nm size range. Using Bacillus anthracis protective antigen domain 4 (D4) as a model antigen, we demonstrated that both amorphous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…However, AH np enhanced the IgG2a production against D4. This is in agreement with our previous results, where it was shown that AH np promotes IgG2a production against D4 [ 41 ]. Similarly, NISV-D4 promoted IgG2a production, which is in agreement with our previous results [ 40 ].…”
Section: Resultssupporting
confidence: 94%
See 4 more Smart Citations
“…However, AH np enhanced the IgG2a production against D4. This is in agreement with our previous results, where it was shown that AH np promotes IgG2a production against D4 [ 41 ]. Similarly, NISV-D4 promoted IgG2a production, which is in agreement with our previous results [ 40 ].…”
Section: Resultssupporting
confidence: 94%
“…Alhydrogel had the slowest antigen release with around 15% antigen release by the 6 th day of analysis, followed by AH np with only around 15% antigen release. This can be correlated to the higher binding coefficient of D4 to alhydrogel and AH np, as was reported in our previous article and by other groups as well [ 41 , 56 , 57 ]. The D4 release kinetics from NISV-D4+ AH np and NISV-D4+ alhydrogel was almost similar.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations